2015
DOI: 10.1016/j.psychres.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition and sleep in mentally disordered patients: A natural experiment in a high security hospital

Abstract: We investigated the relationship between a change in sleep quality and facial emotion recognition accuracy in a group of mentally-disordered inpatients at a secure forensic psychiatric unit. Patients whose sleep improved over time also showed improved facial emotion recognition while patients who showed no sleep improvement showed no change in emotion recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…By contrast, a mixed overall pattern appears regarding the association between sleep and facial emotion recognition (FER), with some studies showing that shortened sleep duration was associated with poorer FER (3842), while others did not or not fully (4346) support such a relationship. In two recent reviews, de Almondes et al (9) found 10 studies on this topic, and Holding et al (44) identified two further investigations (43, 47). A deeper inspection of these 12 studies points toward a broad heterogeneity in study populations, sample size, methodological approaches to assess FER, along with manipulation of sleep duration ranging from no change to 72 h of sleep deprivation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…By contrast, a mixed overall pattern appears regarding the association between sleep and facial emotion recognition (FER), with some studies showing that shortened sleep duration was associated with poorer FER (3842), while others did not or not fully (4346) support such a relationship. In two recent reviews, de Almondes et al (9) found 10 studies on this topic, and Holding et al (44) identified two further investigations (43, 47). A deeper inspection of these 12 studies points toward a broad heterogeneity in study populations, sample size, methodological approaches to assess FER, along with manipulation of sleep duration ranging from no change to 72 h of sleep deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…The present study will address several shortcomings identified in previous research. With regard to the population under study, most investigations focused on young healthy adults (38, 4043, 46, 4851), whereas only two studies assessed clinical samples (45, 47). Kyle et al (45) found that compared to healthy controls ( N = 15), patients with insomnia ( N = 16; mean age of the total sample of 31 participants: 47.1 years, 66% females) showed a decrease in perceived intensity of sad and fearful faces, while no differences were observed as regards the categorization of FER.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While chronic sleep impairments were shown to increase negative emotional reactivity and to play a major role in psychiatric conditions, the sleep disorder's management could lead to negative emotional and altered affective symptoms relief. In this context, Chu et al 2015 [147] showed that sleep improvement and emotional processing (evaluated by facial emotion recognition tasks) were concomitantly occurring in psychiatric disorders patients, while the lack of sleep was significantly associated with the incapacity to recognize angry and fearful expressions, specifically. This could be the reason why sleep quality and duration were reported the best predictors of better outcomes in treating anxiety disorder, as a study on 11-year-old children recently showed [148].…”
Section: Interaction Between Sleep Quality Mental Health and Psychiat...mentioning
confidence: 99%